PENGARUH KEWAJIBAN KEPEMILIKAN NPWP DAN PEMERIKSAAN PAJAK TERHADAP UKURAN PENERIMAAN PAJAK PENGHASILAN (Survey Pada Kantor Pelayanan Pajak Pratama Karawang) - Komalasari, Engkom; Yanti, Yanti; Trisyanto, Ade (Peneliti.net, 2023)
This study aims to determine the effect of NPWP Ownership Obligations and Tax Audits on the Size of Income Tax Receipts (Survey at the Karawang Pratama Tax Service Office). This research method uses quantitative methods with data taken using primary data. The sampling technique was determined by purposive sampling method. The samples taken in this study were 103 individual taxpayers with the criteria of having an NPWP in Karawang. Data collection was carried out by distributing questionnaires via Google Forms. The data analysis method was used to process data in this study using PLS with SmartPLS 3.0 software.